Current status of human papillomavirus vaccination in India's cervical cancer prevention efforts. Issue 11 (November 2019) - Sankaranarayanan, Rengaswamy; Basu, Partha; Kaur, Prabhdeep; Bhaskar, Rajesh; Singh, Gurinder Bir; Denzongpa, Phumzay; Grover, Rajesh K; Sebastian, Paul; Saikia, Tapan; Oswal, Kunal; Kanodia, Rishav; Dsouza, Amantia; et al.
Summary: Efforts are being made to scale up human papillomavirus (HPV) vaccination for adolescent girls in India. Bivalent and quadrivalent HPV vaccines were licensed in the country in 2008, and a nonavalent vaccine was licensed in 2018. Demonstration projects initiated in Andhra Pradesh and Gujarat in 2009 introduced HPV vaccination in public health services in India. Following a few deaths in these projects, although subsequently deemed unrelated to vaccination, HPV vaccination in research projects was suspended. This suspension by default resulted in some participants in a trial evaluating two versus three doses receiving only one dose. Since 2016, the successful introduction of HPV vaccination in immunisation programmes in Punjab and Sikkim (with high coverage and safety), government-sponsored opportunistic vaccination in Delhi, prospects of a single dose providing protection, and future availability of an affordable Indian vaccine shows promise for future widespread implementation and evaluation of HPV vaccination in India.